Pillars of Cloud and Fire : The Politics of Exodus in African American Biblical Interpretation - Marbury, Herbert Robinson (Book collections on Project MUSE., 2015)
At the birth of the United States, African Americans were excluded from the newly-formed Republic and its churches, which saw them as savage rather than citizen and as heathen rather than Christian. Denied civil access to the basic rights granted to others, African Americans have developed their own sacred traditions and their own civil discourses. As part of this effort, African American intellectuals offered interpretations of the Bible which were radically different and often fundamentally oppositional to those of many of their white counterparts. By imagining a freedom unconstrained, their work charted a broader and, perhaps, a more genuinely American identity. In 'Pillars of Cloud and Fire', Herbert Robinson Marbury offers a comprehensive survey of African American biblical interpretation.